2019
DOI: 10.1080/1034912x.2019.1596228
|View full text |Cite
|
Sign up to set email alerts
|

Managing children with challenging behaviours. Parents’ meaning-making processes in relation to their children’s ADHD diagnosis

Abstract: This study investigates parents' lived experiences of having a child diagnosed with Attention Deficit Hyperactivity Disorder (ADHD). The aim was to explore parents' meaning-making processes in relation to their children's ADHD with a focus on understanding the impact that receiving a diagnosis had on the parents' perceptions of, and ways of managing, their children's challenging behaviours. Drawing on data collected through semi-structured interviews with 12 parents, we carried out a content analysis of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Follow-up work could use in-depth interviews in a smaller group of parents with children who experience problems relating to time. However, parental report can only provide insight across a limited range of contexts and perception of the child’s behaviour will invariably be shaped by knowledge of the child’s diagnosis ( Ringer et al, 2020 ). Triangulation would be valuable in future work with the perspective of teachers ( Tobia et al, 2019 ), and the children themselves providing a more complete picture of the impact of timing on everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up work could use in-depth interviews in a smaller group of parents with children who experience problems relating to time. However, parental report can only provide insight across a limited range of contexts and perception of the child’s behaviour will invariably be shaped by knowledge of the child’s diagnosis ( Ringer et al, 2020 ). Triangulation would be valuable in future work with the perspective of teachers ( Tobia et al, 2019 ), and the children themselves providing a more complete picture of the impact of timing on everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results showed no differences in mind-mindedness as a function of children’s diagnostic group, and levels of mind-mindedness were in fact highest in the ADHD group. However, these parents also scored highest for negative mind-minded descriptions, which suggests that parents of children with ADHD may tend to view their children’s behavior as intentional or wilful, or to focus on their cognitive deficits (Ringer et al 2019 ). Parents of children with ASD and ADHD also used the highest levels of negative non-mental descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Corcoran et al [7] about a meta-synthetic and quantitative study that analyses a systematic review of qualitative studies of the life experiences of parents who have children with ADHD showed that anger and the desire to commit suicide existed due to the relentless pressure. In several other qualitative studies with the same objective found that the mothers experienced extreme sadness, shame that caused loneliness, guilt towards the child's siblings [15,5,23] . The feeling of being demanded and isolated that made some mothers felt that home-schooling is the right solution for their children [22] is often experienced by mothers and their children diagnosed with ADHD.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, this study will focus on mothers whose children are diagnosed with ADHD. Qualitative research on parents, especially mothers, and children with ADHD can be seen from the experiences of mothers in raising their children [22] , the pressure or stress experienced [15,10] , also about parents' perceptions of their children who were diagnosed with ADHD and how they manage their children's challenging behaviours [23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation